Barriers of blood donation practices during the pandemic- KAP study on voluntary blood donation during the COVID-19 pandemic among undergraduate students in Karnataka - Kumar, Subhiksha; Thadigotla, Shreya; Lakshmisha, Sripradha; Sullad, Shraddha C.; B., Shivani; Taj, Sobiya; Dewan, Stuti; Chidambaram, Priyadarshini (International Journal Of Community Medicine And Public Health, 2023)
Background: During COVID-19 outbreak there was a drastic reduction in voluntary blood donation and cancellation of blood camps. Students and youth constitute a huge pool of voluntary blood donors and can also educate others in the community. Aim was to assess voluntary blood donation practices and its barriers during the COVID-19 pandemic among undergraduate students in Karnataka and assess knowledge and attitude towards blood donation. Methods: This was a retrospective record analysis of a 2021 online survey data collected as part of a student’s educational research exercise. Records of knowledge, attitudes, and practices of blood donation among undergraduate students were retrieved and analyzed. Results: Of the records of 232 undergraduate students, 64.2% (149) and 62.1% (144) were medical students and females. None of the participants had complete knowledge and there was significant difference in the knowledge of medical and non-medical students regarding blood donation. Satisfactory attitude towards blood donating procedure was seen among 64.2% students. Blood donation had been done by 19% and 4.7% of participants before and during the pandemic, respectively with majority being males and slightly more by non-medical students. Willingness to donate blood in the future was seen among 94.4%. Conclusions: The results suggest the need for awareness campaigns to address misconceptions and improve knowledge and attitude towards blood donation; also, to increase the number of voluntary blood donations as there was a high willingness to donate blood in the future. This could also be translated to other epidemics or pandemics that may arise in the future.